ANALISIS BEBAN PENDINGINAN PADA COLD STORAGE UNTUK PENYIMPANAN DAGING - Fajarani, Ratu Mutia; Handoyo, Yopi; Rahmanto, Raden Hengki (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2019)
Cooling is the best preservation method than others because the food that has been cooled will remain fresh and will not experience a change in taste, color and aroma, besides all the activities that cause decay will stop so that the cooled food will last longer. (Hartanto, 1984). With the proper cooling engine planning, it can help with spatial adjustments, adjustments to loading, estimation of the power to be used, and budget plans. That is what is commonly called the cooling load calculation. Calculation of cooling load needs to be carried out before planning. This is necessary because the magnitude of the pending load is very influential on the selection of the cooling engine so that the freezing point for preserving food can be accurate. Pendiginan burden is influenced by external and internal factors. With the experimental method, it is obtained the results of the external cooling load as the external cooling load is 11.6 kW, the inner cooling load is 138.8 kW and the performance work coefficient (COP) is 2.